Model of parallel planning of logistic and distribution processes - Babić, Darko; Ćavar, Ivana; Průša, Petr (Univerzita Pardubice, 2007)
The logistic activities represent an optimized response to the globalization processes, and the companies involved in such activities, with optimal planning of the logistic and distribution processes, realize higher profit and more stable position on the world market. Therefore, it is necessary to define the logistic and distribution processes, their elements and interrelations, effects, as well as planning process methods, and all this in order to optimize the operation of logistic operators. Logistic-distribution processes are very complex, i.e. they consist of a multitude of details that occur in reality, but cannot influence the planning. Precisely therefore it is necessary to solve the real problems by simplified copies of these problems, the so-called models, as the basis for making a plan. The presentation of the real problem, the simplest possible but with all the necessary details and not ignoring several serious real factors, is called modelling (“art of model creation”). The basic aim of planning the logistic and distribution processes is to achieve the uniformity and consistency i.e. continuity of the goods flows and the best possible usage of the traffic infrastructure and the transport means. Precisely this is of vital importance for the rational realization of the logistic functions, since good exploitation per time and capacity is the basic precondition for reducing the fixed costs which are, as is well known, extremely high in transport. Based on this it is obvious that planning of logistic and distribution processes has to be performed at the level of the entire system, and that it is necessary also to carry out separate planning of elements of the logistic and distribution systems, taking into consideration their interwoven condition, with the aim of creating optimal logistic processes.
Model paralelního plánování logistických a distribučních procesů
Keywords: paralelní plánování; logistické procesy; distribuční procesy; determinace modelů